The Determinants of Intention to use E-voting System: The Case of Generation X in Malaysia (Journal of Business Management and Accounting, 2020)
The internet has opened doors for electronic voting (E-voting). A review of the loopholes of the 14th General Election in Malaysia including the delay of votes from overseas voters, the declaration of a public holiday on voting day and the extraordinary heavy traffic, implies that E-voting could be a better alternative to the paper-based ballot voting. Therefore, the objective of this study is to examine the determinants of the intention to use the E-voting system among Generation X in Malaysia. This study focused only on Generation X because most internet users are from this age group (22 to 37-year olds) compared to other age groups. Hence, Generation X may be the focus of E-voting. A survey of 351 respondents on their intention to use E-voting system was conducted throughout 13 states and the Federal Territory of Kuala Lumpur (Wilayah Persekutuan). Additionally, an empirical model was drawn from adopted theories and data was analyzed using the Partial Least Squares – Structural Equation Modeling (PLS-SEM) approach. The findings showed that compatibility, relative advantages and perceived ease of use significantly contributed to the intention to participate in E-voting. However, perceptions of image, complexity of use, perceived usefulness, trust in the internet and in the government are not significantly related to the intention to use E-voting.